REPRESENTASI KONFLIK MORAL DAN KETIMPANGAN SOSIAL DALAM SISTEM PENDIDIKAN PADA FILM BAD GENIUS (2017) - Sylfani Tridewi; Maulina Larasati Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2026)
Education should fully support the process of moral and intellectual development. In reality, however, education often becomes a competitive arena in which achievement is valued more highly than integrity. This study analyzes how the education system is portrayed in the film Bad Genius (2017) through narrative analysis and Stuart Hall's theory of representation. Using a qualitative approach, the study examines how the film reflects moral conflict, academic competition, and socio-economic inequality as manifestations of structural injustice within the education system. Applying Todorov's narrative model, the study shows how the journey of the main character, Lynn, reflects a moral transformation from an idealistic student into one trapped in a moral dilemma caused by academic pressure and economic limitation. The narrative structure reveals declining morality as a consequence of an education system that consistently prioritizes results over process. Through Hall's theory of representation, the film offers a social critique of an education system in which success is measured by outcomes rather than by the learning process itself. This shows that Bad Genius does not merely highlight academic cheating, but also exposes the injustice of an education system that ultimately shapes students' moral choices. The film illustrates how social and economic dimensions influence ethical decision-making, and underscores the importance of equitable educational policies that support human well-being and moral integrity. The significance of this study lies in offering a critical perspective on the interplay between morality, competition, and social inequality within the education system.